ENTHUSIASM FOR LEARNING ENGLISH IN CHILDREN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Learning a new language, especially English, at an early age opens doors to a world of opportunities for children. However, maintaining their enthusiasm and interest can be challenging. Children are naturally curious and respond well to fun, interactive, and engaging methods of learning. By tapping into their love for stories, games, music, and play, we can nurture their passion for learning English. This introduction aims to explore creative strategies that can boost children's excitement and motivation to learn English in enjoyable and meaningful ways.